Cooperative Interactions in Methanol-Water Mixtures Studied by Microwave Dielectric Data - Chen, Yong-Qiang; Huang, Ying-Shu; Yu, Bo (Asian Journal of Chemistry, 2015)
Based on the dielectric data, the methanol-water mixtures in the water rich region (0-0.1) at 293, 298 and 303 K were performed. We estimated the cooperative interaction of methanol-water cluster by extended Froehlich theory. We get different aspect of the interaction of molecules, which help to understand the relaxation acts.